EVALUATION OF THE REHABILITATION PROGRAM OF UNINHABITABLE HOUSES FOR LOW-INCOME PEOPLE IN SITUMEANG HABINSARAN URBAN VILLAGE - Septiani Solagrasia Lumban Gaol; R. Sally Marisa Sihombing (Yayasan Wayan Marwan Pulungan, 2025)
Tapanuli Regency has been running the Uninhabitable House Rehabilitation Program since 2015 and in 2019 Situmeang Habinsaran Village received assistance from the uninhabitable house rehabilitation program. However, in its implementation, the rehabilitation program for uninhabitable houses that has been running for 8 years has not been able to answer the problem of uninhabitable houses in Situmeang Habinsaran Village. This research uses descriptive research methods with a qualitative approach. The results of this study show that the rehabilitation program for uninhabitable houses in Situmeang Habinsaran Subdistrict from the aspect of effectiveness is not good enough, marked by the repair of houses that are carried out only focused on repairing roofs, floors and walls while other components of house repairs are not repaired. The efficiency and adequacy aspects are not good enough with insufficient human resources and waste of aid funds. Aspects of equity that are not good enough due to the uneven socialization provided. The responsiveness aspect is not responsive to the recipient community and the accuracy aspect, the rehabilitation program for uninhabitable houses is not right on target. The implementation of the Rehabilitation Program for Uninhabitable Houses in Situmeang Habinsaran Village has not gone well and has not achieved its goals.